Sistem Bank Data Wajib Pajak KPP Pratama Pekanbaru Senapelan - Bima Saptayona Winken Somopawiro; Raymond Maulany (TeIKa, 2018)
Kantor Pelayanan Pajak (KPP) Pratama Pekanbaru Senapelan carry out services in the field of taxation to the public within the scope of the KPP Pratapelan working area. At present the Pekanbaru Senapelan KPP Taxpayer data has been stored in the form of digital data. In accordance with the letter of instruction of the Ministry of Finance of the Republic of Indonesia Number: S - 333 / WPJ.02 / 2016, it is briefly stated that each Riau Province KPP must provide and make a media as a Taxpayer Data Storage and Distribution Center. Because of these many needs, the information and data lanes must be efficient and effective in their distribution. The objectives of this research are (1) To build a Pekanbaru Taxpayer Taxpayer Data Bank System. (2) To design the KPP Pekanbaru Senapelan Taxpayer Data Bank System and (3) To implement the KPP Pekanbaru Senapelan Taxpayer Data Bank System. The conclusions of this study are (1) Taxpayer Data Bank System in the KPP Pekanbaru Senapelan to assist the KPP Pekanbaru Senapelan in terms of storing Taxpayer data into a database so that the data is not easily lost or damaged and share the data that has been stored, (2 ) The Taxpayer Data Bank System at KPP Pekanbaru Senapelan has a good appearance so that users can use this system easily because it has a user-friendly display, (3) The Taxpayer Data Bank System on the KPP Pekanbaru Senapelan primarily has access rights to enter into the system so that each user has their own level which will be useful for storing data in accordance with the permissions of the user or other intended user.